Can the Luck of the Draw Help Social Safety Nets? - Bance, Paul; Schnitzer, Pascale (World Bank, Washington, DC, 2021)
Lottery, a simple random draw, has been used in selecting beneficiaries of public work programs in context as diverse as Argentina and the Central African Republic. However, despite a burgeoning literature on targeting, this approach has hardly been studied. This policy note discusses how lotteries compare against other targeting methods in terms of efficiency, legitimacy, and readiness; and if lotteries could be expanded beyond their traditional use for public works to cash transfers. While more research is needed, there is no immediate reason why lotteries should not be used for targeting social safety net interventions, especially when responding to emergencies in ultra-poor and fragile settings.